MINAT REMAJA TERHADAP KESENIAN DIKIA RABANO - Mulia Natasya; Rina Susanti (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2023)
Dikia rabano art is an art with Islamic nuances located in Nagari Panampuang, Ampek Angkek District, Agam Regency West Sumatera. Dikia rabano art is a local cultural property that must be maintained and preserved by the community, especially teenagers. This art is practiced by men aged between 18 and 50 and is usually performed at weddings and the release of pilgrims. Dikia rabano art is usually held at home so that it becomes less attractive to young people and creates different views among young people, especially teenagers. The art of dikia rabano is assimilated with traditional Minangkabau philosophy, namely